Borrelia burgdorferi infection induces long-term memory-like responses in macrophages with tissue-wide consequences in the heart. - Diego Barriales; Itziar Martín-Ruiz; Ana Carreras-González; Marta Montesinos-Robledo; Mikel Azkargorta; Ibon Iloro; Iraide Escobés; Teresa Martín-Mateos; Estibaliz Atondo; Ainhoa Palacios; Monika Gonzalez-Lopez; Laura Bárcena; et al. (PLoS Biology, 2021)
Lyme carditis is an extracutaneous manifestation of Lyme disease characterized by episodes of atrioventricular block of varying degrees and additional, less reported cardiomyopathies. The molecular changes associated with the response to Borrelia burgdorferi over the course of infection are poorly understood. Here, we identify broad transcriptomic and proteomic changes in the heart during infection that reveal a profound down-regulation of mitochondrial components. We also describe the long-term functional modulation of macrophages exposed to live bacteria, characterized by an augmented glycolytic output, increased spirochetal binding and internalization, and reduced inflammatory responses. In vitro, glycolysis inhibition reduces the production of tumor necrosis factor (TNF) by memory macrophages, whereas in vivo, it produces the reversion of the memory phenotype, the recovery of tissue mitochondrial components, and decreased inflammation and spirochetal burdens. These results show that B. burgdorferi induces long-term, memory-like responses in macrophages with tissue-wide consequences that are amenable to be manipulated in vivo.